"Lift Up a Living Nation": Community and Nation, Socialism and Religion in The English Hymnal, 1906. (15th March 2017) - Palmer Heathman, Katie
Abstract: The lead editors of The English Hymnal (1906), Percy Dearmer and Ralph Vaughan Williams, found Victorian hymnody in need of serious revision, and not just aesthetically. This musical book was intended as an expression of the editors' Christian socialist politics involving in the participation of the congregation. This article examines how they achieved this by the encouragement of active citizenship through communal music-making, using folksong tunes alongside texts which affirmed community. This article argues that the editors wedded religion and high-quality music with a focus on citizenship drawn from British Idealism; using a cultural movement to seek social change.